The Impact of SFAS No. 131 Business Segment Data on the Market's Ability to Anticipate Future Earnings - Ettredge, Michael L.; Kwon, Soo Young; Smith, David B.; Zarowin, Paul A. (The Accounting Review, 2005)
This study investigates the effect of firms' adoption of SFAS No. 131 segment disclosure rules on the stock market's ability to predict the firms' earnings, as captured by the forward earnings response coefficient (FERC). The FERC is the association between current-year returns and next-year earnings. SFAS No. 131, effective for fiscal years beginning after December 15, 1997, arguably increased both the quantity and quality of segment disclosure. Consistent with the standard's intended qualitative effects, pre-131 multi-segment firms experienced a significant increase in FERC after adopting SFAS No. 131. Consistent with the standard's intended quantitative effects, many pre-131 single-segment firms began disclosing multiple segments, and those that did experienced an increase in FERC. However, pre-131 single-segment firms that remained single segment (i.e., were unaffected by SFAS No. 131) had no change in FERC, indicating that the increase in FERC for 131-affected firms is not due to some other event concurrent to the adoption of SFAS No. 131. These results are robust under numerous procedures that control for characteristics of the sample firms and their earnings, providing strong evidence that SFAS No. 131 resulted in an increase in stock price informativeness for affected firms. Thus, we provide the first empirical price-based evidence that SFAS No. 131 provided more information (about future earnings) to the market, as the standard's proponents have suggested.